PERAN MODERASI BUDAYA ORGANISASI PADA PENGARUH GAYA KEPEMIMPINAN, KOMITMEN DAN KEPUASAN (Students' Journal of Economic and Management, 2013)
The purpose of this study was to examine and analyze the effect of leadership style on organizational commitment, the moderating effect of organizational culture on the relationship between leadership style and organizational commitment, the effect of organizational commitment on job satisfaction and the moderating effect of organizational culture on the relationship between organizational and job satisfaction on ward nurses in “X” Hospital Tegal. Data obtained by the census on 106 respondents of civil servants ward nurses in “X” Hospital Tegal. Descriptive statistics are reported and continued with, test validity, reliability test, test models and hypothesis testing is done by multiple regression and residual test for moderating variables. Job-Centered leadership style (task-oriented leader) has a positive and significant effect on Affective Commitment. The influence of organizational culture Outcome Orientation may moderate the effect of Job-Centered leadership style to increase Affective Commitment and Continuance Commitment. Affective Commitment and Continuance Commitment has a positive and significant effect on job satisfaction. The influence of organizational culture People Orientation may moderate Affective Commitment and Continuance Commitment to increase job satisfaction, and the influence of organizational culture Outcome Orientation may moderate Affective Commitment to increase job satisfaction. Key Words: leadership style, organizational commitment, organizational culture, job satisfaction